Digital transformation of commercial banks with innovative credit structure - Jingwen Yang; Xiaohui Chen (Journal of Innovation & Knowledge (JIK), 2025)
Digital transformation is widely acknowledged as a pivotal factor in reducing banks' marginal costs and enhancing the efficiency of credit risk management. Concurrently, it allows banks greater flexibility to adapt to shifts in market conditions, thereby optimizing adjustments to credit scale and structure. Despite these recognized benefits, the extant literature has yet to comprehensively analyze the specific mechanisms through which digital transformation impacts banks' credit operations. This study addresses this research gap by examining how digital transformation dynamically affects the supply of bank credit, with the objective of offering valuable insights to bank management and policymakers. This study utilizes panel data from commercial banks and employs a nonlinear difference-in-differences (DID) approach to analyze the mechanisms and determinants of how digital transformation affects the credit supply scale and structure. The findings indicate that while digital transformation via policy guarantees does not significantly alter the overall credit scale, it significantly influences the credit structure, encouraging banks to enhance credit provision to small and micro-enterprises (SMEs). These findings are robust to various tests. This study reveals that the digital transformation mechanism introduces novel data elements for policy guarantees, facilitates the digitalization of banking operations, reduces costs, and improves risk management, thereby steering the credit structure toward SMEs. The impact of digital transformation is not uniform across banks; differences in management and information-screening capabilities lead to heterogeneous effects on credit structures. Notably, the impact of policy-guaranteed digital transformation on credit structure is more pronounced in non-local commercial banks with regional operations. To validate these conclusions, this study examines 2061 loan records from 42 banks, confirming that digital transformation effectively redirects commercial banks' credit supply towards enterprises and the real economy. This research offers theoretical insights for refining policy guarantee frameworks, accelerating the digital transformation of commercial banks, and bolstering their credit support for SMEs.
Keywords: G21; G28; G32; O16; 650; Digital transformation; Innovative credit structure; Commercial banks credit; Combination of the digital economy and the real economy